135: Assessing the Accuracy of Physical Literacy Screening Tasks with the Canadian Assessment of Physical Literacy (CAPL). Issue 5 (1st June 2015) - Longmuir, P; Alpous, A; Borghese, M; Callender, L; Fournier, A; Boyer, C
Abstract: BACKGROUND: Physical literacy is a child's capacity to achieve a healthy, active lifestyle. Leaders in healthcare and allied-health (health) are important partners for identifying children with physical literacy deficits. Current physical literacy assessments are time consuming and require resources not typically available in health settings. OBJECTIVES: We sought to develop and evaluate physical literacy screening tasks that would be suitable for health professionals in a variety of settings. The goal was to enable health professionals to quickly and accurately identify children in the lowest 10th percentile of physical literacy scores. DESIGN/METHODS: Children, eight to 12 years, were recruited from recreation, education and health settings. They performed the Canadian Assessment of Physical Literacy (CAPL), a detailed assessment of a child's capacity for a physically active lifestyle. Children also answered simple questions about their own physical activity and performed eight potential physical literacy screening tasks, including one test of strength, two balance tests, one endurance test, and four motor skills assessments. Children were grouped as above/below the 10th percentile for CAPL score. Sensitivity and specificity scores for each screening task, and for combined pairs of screening tasks were calculated based on the 10th percentile groups. RESULTS: Study protocols were completed by 105 children (52.4% female). Sensitivity of individual test items to identify children below the 10th percentile for CAPL score ranged from 60% to 100%. Specificity for individual scores ranged from 9.6% to 87.8%. Two combination protocols were identified as having high specificity and sensitivity. Each combination contained two screening tasks: a) holding a one-leg balance test on the left leg for less than 34 seconds and a wall sit for less than 33 seconds (80.0% sensitivity, 93.3% specificity), and b) holding a one-leg balance test on the left leg for less than 40 seconds and self-reporting an activity level, as compared to their peers, below 6 out of 10 (60.0% sensitivity, 93.0% specificity). The positive predictive value of these protocols was high (98.8% and 97.9%, respectively). CONCLUSION: Two sensitive and specific physical literacy screening protocols for children eight to 12 years of age were identified for health settings. Reliability of the screening protocols and effectiveness of the screening task educational materials are on-going. Future research should evaluate the suitability of the screening tasks for children with identified disabilities/chronic illnesses, and the ability of healthcare and allied-health professionals to implement the screening tasks and utilize the results obtained for patient care.